2014
DOI: 10.3233/jhd-140127
|View full text |Cite
|
Sign up to set email alerts
|

Aggression in Huntington's Disease: A Systematic Review of Rates of Aggression and Treatment Methods

Abstract: Aggression is commonly reported in individuals with Huntington's disease (HD). While correlating factors for aggression are often speculated about, features that are associated with, and contribute to, aggression in this population have not been clearly determined. This systematic review investigates rates of aggression and treatment options for aggression in HD. A number of key findings were revealed. Studies reporting on rates of aggression revealed that its prevalence is high, falling between 22 and 66 perc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 53 publications
(26 citation statements)
references
References 47 publications
0
25
0
1
Order By: Relevance
“…mouse model with elevated aggression and exercise was found to ameliorate aggressive behavior through activation of the reeling signaling pathway [Seo et al, 2013]. Aggressive behaviors are common in many neurological and psychiatric disorders including neurodegenerative disorders [Burns et al, 1990;Fisher et al, 2014;Oh et al, 2015], developmental disabilities [Rojahn et al, 1993], schizophrenia [Sandyk, 1993], bipolar disorder [Ballester et al, 2012], ADHD [Cha et al, 2015],and autism [Pivovarciova et al, 2014]. Epidemiologic and molecular genetic studies show that many disorders share genetic variants in common, suggesting common underlying molecular mechanisms [de Lacy and King, 2013;Lichtenstein et al;Smoller et al, 2013].…”
Section: Figmentioning
confidence: 99%
“…mouse model with elevated aggression and exercise was found to ameliorate aggressive behavior through activation of the reeling signaling pathway [Seo et al, 2013]. Aggressive behaviors are common in many neurological and psychiatric disorders including neurodegenerative disorders [Burns et al, 1990;Fisher et al, 2014;Oh et al, 2015], developmental disabilities [Rojahn et al, 1993], schizophrenia [Sandyk, 1993], bipolar disorder [Ballester et al, 2012], ADHD [Cha et al, 2015],and autism [Pivovarciova et al, 2014]. Epidemiologic and molecular genetic studies show that many disorders share genetic variants in common, suggesting common underlying molecular mechanisms [de Lacy and King, 2013;Lichtenstein et al;Smoller et al, 2013].…”
Section: Figmentioning
confidence: 99%
“…, Bushman & Anderson , Fisher et al . ). It is as an externalised behaviour that can be directly observed and measured via observation from carers, family members and hospital staff (Fisher et al .…”
Section: Introductionmentioning
confidence: 97%
“…It is as an externalised behaviour that can be directly observed and measured via observation from carers, family members and hospital staff (Fisher et al . ). A recent systematic review has revealed high prevalence rates for aggression, across multiple samples, ranging between 22–66% of HD sufferers (Fisher et al .…”
Section: Introductionmentioning
confidence: 97%
See 2 more Smart Citations